Data-precoded algorithm for multiple-relay-assisted systems - Teodoro, Sara (2012)
A data-precoded relay-assisted (RA) scheme is proposed for a system cooperating with multiple relay nodes (RNs), each equipped with either a single-antenna or a two-antenna array. The classical RA systems using distributed space-time/frequency coding algorithms, because of the half-duplex constraint at the relays, require the use of a higher order constellation than in the case of a continuous link transmission from the base station to the user terminal. This implies a penalty in the power efficiency. The proposed precoding algorithm exploits the relation between QPSK and 4 L -QAM, by alternately transmitting through L relays, achieving full diversity, while significantly reducing power penalty. This algorithm explores the situations where a direct path (DP) is not available or has poor quality, and it is a promising solution to extend coverage or increase system capacity. We present the analytical derivation of the gain obtained with the data-precoded algorithm in comparison with distributed space-frequency block code (SFBC) ones. Furthermore, analysis of the pairwise error probability of the proposed algorithm is derived and confirmed with numerical results. We evaluate the performance of the proposed scheme and compare it relatively to the equivalent distributed SFBC scheme employing 16-QAM and non-cooperative schemes, for several link quality scenarios and scheme configurations, highlighting the advantages of the proposed scheme.